Analisis Kinerja Keuangan Berdasarkan Laporan Keuangan Tahunan Perusahaan Periode 2017–2025: Studi Kasus pada PT Campina Ice Cream Industry, Tbk. - Pandu Dewanata (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study aims to analyze the financial performance of PT Campina Ice Cream Industry, Tbk., an ice cream manufacturer listed on the Indonesia Stock Exchange, during the period 2016–2025 with a focus on the 2017–2025 range. The research method used is qualitative descriptive by combining financial ratio analysis and SWOT analysis. Secondary data is obtained from the company's annual reports as well as official financial statements. The ratios studied include liquidity ratio (current ratio), solvency ratio (debt to asset ratio), profitability ratio (net profit margin and return on equity), and activity ratio (total asset turnover). Trend analysis is done through various visualizations such as line charts, bar charts, stacked bar charts, waterfall charts, heatmaps, and key performance indicators (KPI) dashboards. The results show that the company has very strong liquidity and is free of long-term bank debt since 2018, reflecting a conservative capital structure. Profitability peaked in 2023, but declined in the following period due to rising operating expenses and raw material prices, despite continued sales growth. The SWOT analysis identified weaknesses in the form of idle production assets and high dependence on the two main modern retail distributors. The study's conclusions confirm that the company's main challenge is to convert sustainable sales growth into higher net profit through cost efficiency and asset optimization.